Effect of a nurse-led hypertension management program on quality of life, medication adherence and hypertension management in older adults: A randomized controlled trial - ERGÜN, AYŞE (WILEY, 2020)
Aim This study evaluated the effects of a nurse-led hypertension management program on quality of life, medication adherence and hypertension management in older adults. Methods A total of 74 hypertensive older adults residing in two different nursing homes were randomized to the intervention group (n= 37) or control group (n= 37). The intervention group participated in a training program consisting of 20 weeks of health education and motivational meetings. Data were collected using a hypertension management knowledge and behavior questionnaire, quality of life scale, Morisky Medication Adherence Scale, and measurements of blood pressure and anthropometric and biochemical parameters. Data were analyzed using the chi(2)-test, Wilcoxon signed-rank test and Mann-WhitneyU-test. Results Post-test systolic (118.64 +/- 10.04 mmHg) and diastolic (77.83 +/- 5.34 mmHg) blood pressures, and total cholesterol levels (178.43 +/- 25.59 mg/dL) were significantly lower in the intervention group compared with the control group (130.54 +/- 15.08 mmHg, 82.70 +/- 7.69 mmHg, 200.7 +/- 34.57 mg/dL, respectively). Post-test hypertension knowledge score (20.75 +/- 1.01), medication adherence rate (100.0%), and quality of life scale physical component (58.42 +/- 13.93) and mental component (64.24 +/- 12.85) scores were significantly higher in the intervention group than in the control group (12.21 +/- 2.48; 64.9%; 44.36 +/- 16.73; 53.93 +/- 15.71, respectively). In addition, mean post-test body mass index (27.19 +/- 4.62 kg/m(2)), weight (74.81 +/- 15.33 kg), waist circumference (93.29 +/- 15.20 cm), hip circumference (107.67 +/- 14.05 cm) and total cholesterol (178.43 +/- 25.59 mg/dL) values were lower than pretest (28.13 +/- 4.96 kg/m(2); 77.37 +/- 16.56 kg; 97.83 +/- 16.23 cm; 112.89 +/- 14.37 cm; 194.78 +/- 38.64 mg/dL, respectively) in the intervention group. Conclusions The nurse-led hypertension management program implemented in this study provides an example of an effective program to guide nurses who work with older adults.Geriatr Gerontol Int 2020; center dot center dot: center dot center dot-center dot center dot.
Keywords: hypertension; hypertension management; older adults; quality of life; STRESS-MANAGEMENT; BLOOD-PRESSURE; EDUCATION; EXERCISE